Anatomy and Biomechanics of the Posterior Cruciate Ligament - Lynch, Thomas B.; Chahla, Jorge; Nuelle, Clayton W. (The Journal of Knee Surgery, 2021)
Posterior cruciate ligament (PCL) injuries are often encountered in the setting of other knee pathology and sometimes in isolation. A thorough understanding of the native PCL anatomy is crucial in the successful treatment of these injuries. The PCL consists of two independent bundles that function in a codominant relationship to perform the primary role of resisting posterior tibial translation relative to the femur. A secondary role of the PCL is to provide rotatory stability. The anterolateral (AL) bundle has a more vertical orientation when compared with the posteromedial (PM) bundle. The AL bundle has a more anterior origin than the PM bundle on the lateral wall of the medial femoral condyle. The tibial insertion of AL bundle on the PCL facet is medial and anterior to the PM bundle. The AL and PM bundles are 12-mm apart at the center of the femoral origins, while the tibial insertions are more tightly grouped. The different spatial orientation of the two bundles and large distance between the femoral centers is responsible for the codominance of the PCL bundles. The AL bundle is the dominant restraint to posterior tibial translation throughout midrange flexion, while the PM bundle is the primary restraint in extension and deep flexion. Biomechanical testing has shown independent reconstruction of the two bundles that better reproduces native knee biomechanics, while significant differences in clinical outcomes remain to be seen. Stress X-rays may play an important role in clinical decision-making process for operative versus nonoperative management of isolated PCL injuries. Strong understanding of PCL anatomy and biomechanics can aid surgical management.
Keywords: PCL; biomechanics; anatomy